Progesterone's Effects on Cognitive Performance of Male Mice Are Independent of Progestin Receptors but Relate to Increases in GABAA Activity in the Hippocampus and Cortex - Frye, Cheryl A.; Lembo, Vincent F.; Walf, Alicia A. (Frontiers in Endocrinology, 2021)
Progestogens' (e.g., progesterone and its neuroactive metabolite, allopregnanolone), cognitive effects and mechanisms among males are not well-understood. We hypothesized if progestogen's effects on cognitive performance are through its metabolite allopregnanolone, and not actions via binding to traditional progestin receptors (PRs), then progesterone administration would enhance performance in tasks mediated by the hippocampus and cortex, coincident with increasing allopregnanolone concentrations, brain derived neurotrophic factor (BDNF) and/or muscimol binding of PR knock out (PRKO) and wild-type PR replete mice. Experiment 1: Progesterone (4 mg/kg, subcutaneously (SC; n = 12/grp), or oil vehicle control, was administered to gonadally-intact adult male mice PRKO mice and their wild-type counterparts and cognitive behaviors in object recognition, T-maze and water maze was examined. Progesterone, compared to vehicle, when administered post-training increased time investigating novel objects by the PRKO and wild-type mice in the object recognition task. In the T-maze task, progesterone administration to wild-type and PRKO mice had significantly greater number of spontaneous alternations compared to their vehicle-administered counterparts. In the water maze task, PRKO mice administered vehicle spent significantly fewer seconds in the quadrant associated with the escape platform on testing compared to all other groups. Experiment 2: Progesterone administered to wild-type and PRKO mice increased plasma progesterone and allopregnanolone levels (n = 5/group). PRKO mice had higher allopregnanolone levels in plasma and hippocampus, but not cortex, when administered progesterone and compared to wild-type mice. Experiment 3: Assessment of PR binding revealed progesterone administered wild-type mice had significantly greater levels of PRs in the hippocampus and cortex, compared to all other groups (n = 5/group). Wild-type mice administered progesterone, but not vehicle, had increased BDNF levels in the hippocampus, but not the cortex, compared to PRKOs. Wild-type as well as PRKO mice administered progesterone experienced significant increases in maximal GABAA agonist, muscimol, binding in hippocampus and cortex, compared to their vehicle-administered counterparts. Thus, adult male mice can be responsive to progesterone for cognitive performance, and such effects may be independent of PRs trophic actions of BDNF levels in the hippocampus and/or increases in GABAA activity in the hippocampus and cortex.